Associative Factors Involved in Avoidance of Exclusive and Non-Exclusive Breastfeeding after C-section - Rahman, Asbah; Malik, Qudrat Ullah; Shafiq, Muhammad Faisal; Mumtaz, Shaista; Babar, Muhammad Waleed; Akram, Saira (Pakistan Armed Forces Medical Journal, 2022)
Objective: To look for the associative factors in avoidance of exclusive and non-exclusive breastfeeding among mothers after lower segment Caesarean section.Study Design: Cross-sectional study.Place and Duration of Study: Paediatrics department, Pak Emirates Military Hospital, Rawalpindi Pakistan from Oct to Mar 2020.Methodology: Mothers bringing their infants for vaccination at six weeks of age with babies born with lower segment caesarean section were included in the study. They were asked simple questions regarding exclusive or non-exclusive breastfeeding. Relevant socio-demographic factors were also recorded and compared among mothers breastfeeding their babies and those avoiding it.Results: A total of 500 mothers were included in the study. The mean age of the study participants was 33.576±9.174 years. 336(67.2%) women were primiparous, while 164(32.8%) were multiparous. 208(41.6%) women were actively breastfeeding their child, while 292(58.4%) avoided breastfeeding their babies. 150(72.1%) women were non-exclusively breastfeeding, while 58(27.9%) showed an exclusive breastfeeding pattern. Pearson chi-square test revealed that low education and working outside the home had a statistically significant association with the avoidance of breastfeeding the babies among our target population (p-value